SOCIO-CULTURAL SETTING IN THE NOVEL A BREATH OF FRESH AIR BY AMULYA MALLADI - Kartiwi, Kintania (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
The novel A Breath of Fresh Air by Amulya Malladi depicts the social and cultural aspects of Indian society at that time. This study aims to describe the social and cultural background in the novel, as well as to examine the ethics contained within Amulya Malladi's work. It was conducted using a qualitative descriptive method, with observation as the data collection technique. The study's results reveal that the novel contains cultural elements based on Koentjaraningrat's theory, including: language (six data points), knowledge systems (two data points), social organisation systems (eight data points), tools and technology systems (nine data points), livelihood systems (three data points), religious systems (five data points), and arts (two data points). The most prominent cultural element in Amulya Malladi's novel is the technological system.